Burung Gosong Filipina (Megapodius cumingii) di Sulawesi Tengah: Variasi Haplotipe dan Hubungan Filogenetik Berdasarkan Gen EEF2 - Novitasari,; Budiarsa, I Made; Suleman, Samsurizal M.; Kundera, I Nengah; Jayanti, Zulaikhah Dwi; Trianto, Manap (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the variation in haplotype distribution and phylogenetic relationships of the Philippine scrub fowl based on the EEF2 gene. Eggshell samples were obtained from Tolitoli and Luwuk, Central Sulawesi. DNA isolation followed the gSYNCTM Extraction Kit protocol, and the amplification process was carried out in 38 cycles, including the pre-denaturation stage (95°C, 5 minutes), denaturation stage (95°C, 45 seconds), annealing stage (53°C, 40 seconds), elongation stage (72°C, 1 minute), and post-elongation stage (72°C, 10 minutes), followed by sequencing. Sequence editing was performed using GeneStudio, sequence alignment and phylogenetic tree reconstruction using MEGA 11, and haplotype network reconstruction using DnaSP and PopART. The results showed that the haplotype network based on the EEF2 gene formed three haplotypes, with the population from Tolitoli having a widespread haplotype, while the population from Luwuk had a specific haplotype. In addition, based on the results of phylogenetic tree reconstruction, it was found that the Philippine white-eye birds from Tolitoli and Luwuk were in the same clade but there was genetic variation between populations.